Penelitian korelasi plasticizer dop dan filler serbuk kayu meranti untuk acuan sepatu - Irene Sri Sukaeni (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 1994)
This research is to find out correlation of using DOP plasticier and Shorea Parvifolis Dyer wood flour filler to physical properties of PVC compound for shoe lasting. PVC compound is made from PVC resin added by other ingredients as plasticizer, stabilizer, lubricant and filler. Ingredient used in this research is DOP, Expoxy oil, BaCdZn, Stearic acid, CaCO3 filler and wood flour by variation of DOP and filler percentage. PVC compound produced is tested its physical properties for hardness, impact strength and tensil strength. Data prove that there is correlation between the physical test and percentage of DOP and wood flour filler fulfilling multiple linier regression for hardness and multiple quadratis regression for impact strength and tensile strength. INTISARI Penelitian ini bertujuan untuk mengetahui korelasi penggunaan plasticier DOP dan filler serbuk kayu meranti terhadap sifat-sifat fisika kompon PVC untuk acuan sepatu. Kompon PVC dibuat dari bahan baku resin PVC dengan ditambah ingredient lain yang berfungsi sebagai plasticizer, stabailizer, lubricant dan filler. Pada penelitian ini ingredient yang dipergunakan adalah : DOP, Epoxy oil, BaCdZn, asam stearat serta filler CaCO3 dan sebuk kayu meranti dengan variasi persentase DOP dan filler serbuk kayu. Kompon PVC yang dihasilkan diuji sifat fisikanya menunjukkan adanya korelasi antara uji fisika tersebut denga persentase DOP dan filler serbuk kayu dengan memenuhi persamaan regresi linier multipel untuk kekerasan dan regresi kuadratis multipel untuk uji ketahanan pukul takik dan kekuatan tarik.